Characterization of somatic structural variations in 528 Chinese individuals with Esophageal squamous cell carcinoma - Heyang Cui; Yong Zhou; Fang Wang; Caixia Cheng; Weimin Zhang; Ruifang Sun; Ling Zhang; Yanghui Bi; Min Guo; Yan Zhou; Xinhui Wang; Jiaxin Ren; et al. (Nature Communications, 2022)
The biological and clinical implications of high genome instability in esophageal squamous cell carcinoma (ESCC) remain to be explored. Here, the authors analyse 528 whole genomes and investigate the landscape and molecular mechanisms underlying structural variations in ESCC patients.